Analysis of the Influence of Teacher Professional Competence and Work Discipline on Teacher Performance at Vocational High Schools in Samarinda City - Harliansyah, Harliansyah (PT Literasi Nusantara Publisher, 2022)
Teacher competence is one of the important substances in the progress and success of the implementation of education. This has implications for teacher performance to measure teacher professional competence in schools. Therefore, this study aims to determine the effect of teacher professional competence and work discipline on teacher performance. This study uses a quantitative approach. Data collection was carried out using a survey method using a questionnaire that was distributed to 22 teachers of public vocational high schools in Samarinda City. The results of the study show that the correlation coefficient between professional competence and work discipline is 0.636, so it can be said that there is a positive relationship between professional competence and work discipline with teachers. Meanwhile, the coefficient of determination is 0.636, meaning that professional competence affects work discipline by 63.6%. Based on this, it is known that the professional competence of teachers in the high category is 58%, the medium category is 42%, and there is no teacher professional competence in the low category. So, it can be concluded that there is a positive and significant influence between professionalism on teacher performance, teacher professionalism, and work discipline together on teacher performance.